Pendampingan Bimbingan Sholat Kepada Anak-Anak Tpq Di Dusun Tambaksari Desa Kebonrejo Kecamatan Kepung Kabupaten Kediri - Muhammad Abu Zaeni (LP3M IAIFA Kediri, 2023)
Tpq is a place for religious education in which it provides learning about religious knowledge, especially the knowledge of reading the Qur'an. From this context, the authors not only provide learning to read the Qur'an, but also provide assistance in learning the basics of prayer. In Islam, prayer is a non-negotiable act of worship. Unlike the case with zakat, fasting and pilgrimage. Zakat, people who are obliged to pay zakat are people who can afford it. Fasting, people who travel long distances or travelers and sick people who have met the requirements, are allowed not to fast. Hajj, a person who is obliged to perform Hajj only people who can afford both in the form of wealth and energy. But unlike the case with prayer, the rich, poor, healthy, sick, male, female, muqim, traveler, all of them are still obliged to pray. Therefore, the author provides assistance in learning prayer for the children of Tpq Dsn. Tambaksari Ds. Kebonrejo district. The siege that the author tucked into learning the Qur'an once a week after sunset. In this study, the author uses the PAR (Participatory Action Research) method by providing an explanation of the basics of prayer and practicing it. In prayer training mentoring, good communication emerged between the author and the children in the tpq so that it could lead to collaboration that could make the prayer training mentoring program a success. The real evidence produced from this prayer guidance mentoring activity is (1) Journals that have ISSN. (2) The services resulting from this prayer guidance assistance activity can provide additional knowledge to children of Tpq Dsn. Tambaksari in order to be able to carry out prayers properly and correctly, both in terms of reading and prayer movements